2021
DOI: 10.3390/horticulturae7080219
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose Enhances Anthocyanin Accumulation in Torenia by Promoting Expression of Anthocyanin Biosynthesis Genes

Abstract: We examined the effects of different sucrose concentrations (3%, 5%, and 7%) on anthocyanin accumulation and plant growth in wild type (WT) and transgenic (T2) torenia cultivar “Kauai Rose” overexpressing the anthocyanin regulatory transcription factors B-Peru + mPAP1 or RsMYB1. Sucrose increased anthocyanin production in both WT and transgenic plants, with higher anthocyanin production in transgenic plants compared to WT plants. Higher sucrose concentrations increased production of anthocyanin in transgenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(69 reference statements)
0
1
0
Order By: Relevance
“… Hase et al (2010) verified that petunia seedlings treated with 3% sucrose could accumulate significant amount of anthocyanin. A similar phenomenon has been reported in torenia ( Torenia fournieri ) leaves ( Naing et al, 2021 ) and postharvest peaches ( Prunus persica ) peel ( Tian et al, 2022 ). Compared to glucose and fructose, sucrose is the most effective and specific activator of anthocyanin biosynthesis in Arabidopsis seedlings ( Solfanelli et al, 2006 ).…”
Section: Discussionsupporting
confidence: 77%
“… Hase et al (2010) verified that petunia seedlings treated with 3% sucrose could accumulate significant amount of anthocyanin. A similar phenomenon has been reported in torenia ( Torenia fournieri ) leaves ( Naing et al, 2021 ) and postharvest peaches ( Prunus persica ) peel ( Tian et al, 2022 ). Compared to glucose and fructose, sucrose is the most effective and specific activator of anthocyanin biosynthesis in Arabidopsis seedlings ( Solfanelli et al, 2006 ).…”
Section: Discussionsupporting
confidence: 77%
“…The synthesis of hypericin and hyperforin compounds in Hypericum perforatum plants is greatly affected by water imbalance and osmotic pressure (David et al, 2016 ; Naik et al, 2016 ; Kladar et al, 2017 ). Moreover, increased levels of sucrose in growth media have been found to induce anthocyanin biosynthesis in callus cultures of Malus domestica (Liu et al, 2017 ) and Torenia fournieri (Naing et al, 2021 ). In Brassica oleracea var.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the detailed information of sugars serving as signal molecules to regulate anthocyanin biosynthesis largely has not been revealed. A few studies suggested that this process was related to the regulation of gene expression levels involved in anthocyanin biosynthesis ( Weiss, 2000 ; Rolland et al, 2002 ; Rook and Bevan, 2003 ; Mol et al, 2008 ; Naing et al, 2021 ). For example, in radish hypocotyl, the anthocyanin accumulation caused by sucrose treatment was related to higher transcripts of CHS and ANS ( Hara et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%